(untitled) (Contemporary Journal of Social Science Review, 2024)
The COVID-19 pandemic has significantly disrupted the global hospitality industry, leading to unprecedented challenges for hotel employees. This study investigates the impact of Transformational Leadership (TFL) on employee burnout, with a focus on the mediating effects of personal financial stress, anxiety, and workplace loneliness. Additionally, the moderating role of Human Resource Management (HRM) practices in the relationship between TFL and burnout is explored. Utilizing the Job-Demands Resources (JD-R) and Conservation of Resources (COR) theories, data were collected from frontline hotel employees during the pandemic. The findings reveal that TFL reduces employees’ personal financial stress, anxiety, and workplace loneliness, which are key factors influencing employee well-being. However, contrary to expectations, TFL does not have a direct impact on burnout, nor do the mediators (financial stress, anxiety, and loneliness) significantly affect the TFL-burnout relationship. This suggests that while TFL alleviates certain job stressors, it does not directly mitigate burnout through these mechanisms. Furthermore, HRM practices did not moderate the relationship between TFL and burnout, indicating that organizational practices alone may not be sufficient to buffer the adverse effects of job stressors during a crisis. The study underscores the complexity of leadership and burnout dynamics in the hospitality sector, especially during crises like the COVID-19 pandemic. It highlights the need for a more comprehensive approach to address burnout, considering additional factors beyond leadership style and stress mediators. These findings contribute to the existing literature on leadership and employee well-being, particularly in the underexplored context of the hospitality industry, and suggest future research directions to better understand and mitigate burnout in high-stress environments.